Pilosella riloensis (Asteraceae), a new hybridogenous species and nomenclatural notes on P. pseudopilosella in Bulgaria - Szeląg, Zbigniew; Vladimirov, Vladimir (Phytotaxa, 2025)
Pilosella riloensis is a new, triploid species from the subalpine zone in the Rila Mountains, Bulgaria. It combines the morphological features of P. kalinensis which belongs to the P. alpicola agg., and Hieracium pseudopilosella subsp. sericochrotum which has been raised to species level as Pilosella sericochrota and typified. The new species was analyzed karyologically using the flow cytometry, and is illustrated with photos of the holotype and details of capitulum in the wild.